Risk Factors for Suboptimal Bowel Preparation for Colonoscopy in Pediatric Patients. Issue 1 (July 2021) - Reddy, Pooja; Mencin, Ali; Lebwohl, Benjamin
ABSTRACT: Background/Aims: Suboptimal bowel cleansing is common in children and can impact diagnostic and therapeutic outcomes. We aimed to identify risk factors for suboptimal bowel preparation for colonoscopy in pediatric patients. Methods: This was a retrospective study of all patients ages 0 to 21 years who underwent colonoscopy at a children's hospital from 2015 to 2019 in the United States. Demographics and clinical information were obtained from the electronic health record. The primary outcome was suboptimal bowel preparation measured by the endoscopist on a dichotomized Aronchik Scale. Univariate and multivariate regression modeling were used to determine independent predictors of suboptimal preparation. Results: Nine hundred and eight patients (mean age 12.17 years [±5.14], boys 465 (51.2%), were included in the analysis. Suboptimal preparation was noted in 242 (26.7%). On univariate analysis, suboptimal preparation was more common in those of younger age (38.6%), Medicaid (32.1%), Spanish as primary language (35.7%), and failure to thrive (FTT) (45.9%). Suboptimal preparations were less common in patients with inflammatory bowel disease (IBD) (11.6%). After adjustment for other covariates, IBD and FTT maintained their statistical associations, IBD (odds ratio [OR] 0.27 95% confidence interval [CI] 0.095–0.75, P = 0.01), FTT (OR 1.98 95% CI 1.28–3.06, P = <0.01). Conclusions: To our knowledge, this is the first investigation of pediatric patients to identify independent risk factors for suboptimal bowel preparation. We confirm Medicaid status and English as a second language as risk factors as well as highlight distinct associations from those reported in the adult literature including FTT and younger age. IBD was associated with optimal cleansing. Future research to understand the mechanisms of inferred risk or potential protection is required.